TECHNOLOGY IMPLEMENTATION STRATEGIES IN EDUCATION: A LITERATURE ANALYSIS - Sigit Sugiardi; Mujahidin (Adisam Publisher, 2025)
Effective strategies for technology implementation in education were found to require a multidimensional approach, involving the integration of adequate technology infrastructure, continuous training for teaching staff, and adaptation of the curriculum to suit technological developments. In addition, collaboration among stakeholders, including government, schools, technology providers and communities, was found to be a key factor in overcoming implementation challenges, such as inequality of access and resistance to change. Policies that are inclusive and orientated towards sustainable solutions are essential in ensuring that technology implementation can improve the quality of education effectively and thoroughly.